Teaching Strategies Used By English Teacher For Writing Descriptive Text In Vocational High School - Andre Silitonga; Yeni Erlita (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2025)
This study aimed to (1) analyze the teaching strategies used by the English teacher in teaching writing descriptive text at a Vocational High School, and (2) describe how these strategies were implemented during the teaching and learning process. The research employed a descriptive qualitative approach, which is suitable for exploring and understanding the detailed aspects of teacher strategies in a natural classroom setting. The data in this study were collected through two main techniques: classroom observations and in-depth interviews with the teacher. The collected data were then analyzed using three stages of qualitative data analysis, namely data reduction, data display, and conclusion drawing, as proposed by Miles and Huberman. The findings of this study revealed that the English teacher applied five teaching strategies that align with the framework proposed by Haynes and Zacarian (2010). These strategies included: (1) determining key concepts, (2) making the lesson visual, (3) linking new information to students’ prior knowledge, (4) providing comprehensible input, and (5) modifying vocabulary to suit students’ language proficiency levels. the implementation of these strategies was integrated into the Modeling of the Text stage, which is a crucial phase in the Genre-Based Approach. This stage allowed the teacher to guide students in analyzing and understanding the structure and language features of descriptive texts before attempting to write their own. As a result of this approach, students demonstrated improved comprehension of the material, increased attentiveness during the lesson, and greater participation in class activities. These strategies were found to be effective in helping students engage with the lesson content more meaningfully.   Keywords: Teaching Strategies, Teaching Writing, Descriptive Text.